Effects of progressive muscle relaxation on health-related outcomes in cancer patients: A systematic review and meta-analysis of randomized controlled trials. (November 2022) - Tan, Lanhui; Fang, Pei; Cui, Jiaxin; Yu, Huidan; Yu, Liping
Abstract: Background and purpose: Progressive muscle relaxation training (PMRT) has been widely applied to improve the physical and mental health of patients. The aim of this study was to evaluate the effects of PMRT on the symptoms and quality of life (QOL) of cancer patients. Methods: Nine databases (Web of Science, CENTRAL, PubMed, Embase, CINAHL, OpenGrey, CNKI, Wanfang, and VIP database) were searched to identify randomized controlled trials (RCTs) that assessed the effects of PMRT on health-related outcomes for cancer patients. The risk of bias of the included studies and the evidence quality were appraised using the Cochrane Risk of Bias 2.0 tool and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach, respectively. Meta-analysis was performed using RevMan 5.4. Results: Twelve RCTs sampling 1147 patients were included. PMRT showed significant effects of alleviating anxiety [standardized mean difference (SMD) = −1.32, 95% CI (−1.88, −0.75), P  < 0.001] and pain [SMD = −1.02, 95% CI (−1.93, −0.11), P  = 0.030], and improving QOL [SMD = 1.65, 95% CI (0.53, 2.76), P  = 0.004] in cancer patients. Regarding depression, self-esteem, nausea, and vomiting, PMRT showed better effects compared to the control group. However, no significant effect of reducing fatigue was detected [SMD = −1.00, 95% CI (−2.27, 0.27), P  = 0.120]. The overall quality of evidence was moderate to very low. Conclusion: PMRT is a promising complementary therapy that may improve the health-related outcomes of cancer patients. Future studies with rigorous research design are needed to obtain valid conclusions. Highlights: Progressive muscle relaxation training may be a promising therapy for physical and mental health of cancer patients. Progressive muscle relaxation training has benefits for improving the quality of life of cancer patients. More well-designed studies are needed to confirm the benefits of progressive muscle relaxation training for cancer patients.